2017
DOI: 10.1093/eurheartj/ehx381
|View full text |Cite
|
Sign up to set email alerts
|

Staging classification of aortic stenosis based on the extent of cardiac damage

Abstract: AimsIn patients with aortic stenosis (AS), risk stratification for aortic valve replacement (AVR) relies mainly on valve-related factors, symptoms and co-morbidities. We sought to evaluate the prognostic impact of a newly-defined staging classification characterizing the extent of extravalvular (extra-aortic valve) cardiac damage among patients with severe AS undergoing AVR.Methods and resultsPatients with severe AS from the PARTNER 2 trials were pooled and classified according to the presence or absence of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
327
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 476 publications
(364 citation statements)
references
References 43 publications
19
327
1
17
Order By: Relevance
“…The CpcPH group had the worst right ventricular function as expressed by TAPSE, an established prognostic marker in various settings, and reflected by the highest right atrial pressure and right ventricular end‐diastolic pressure. The presence of right ventricular dysfunction represents the most advanced stage of AS, which is associated with poor prognosis . There is relatively recent evidence that in patients with severe AS, PH often persists after AVR, and that post‐AVR PH is a more important prognostic predictor than pre‐AVR PH .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CpcPH group had the worst right ventricular function as expressed by TAPSE, an established prognostic marker in various settings, and reflected by the highest right atrial pressure and right ventricular end‐diastolic pressure. The presence of right ventricular dysfunction represents the most advanced stage of AS, which is associated with poor prognosis . There is relatively recent evidence that in patients with severe AS, PH often persists after AVR, and that post‐AVR PH is a more important prognostic predictor than pre‐AVR PH .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of right ventricular dysfunction represents the most advanced stage of AS, which is associated with poor prognosis. 3 There is relatively recent evidence that in patients with severe AS, PH often persists after AVR, 5,6 and that post-AVR PH is a more important prognostic predictor than pre-AVR PH. 5 Since this information is derived from echocardiographic studies, the detailed haemodynamic pattern prior and post AVR of these patients remains unknown.…”
Section: Prognostic Importance Of Combined Pre-and Post-capillary Pulmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Pulmonary hypertension (PH) is a common finding in patients with AS, especially postcapillary PH due to left heart disease, the most common type of PH. [2][3][4][5][6][7][8][9][10][11] Pulmonary hypertension is a sign of advanced cardiac damage due to severity of AS according to damage stages 3 and 4 as described by Genereux et al 12 Previous studies in patients with PH showed an increased mortality after aortic valve replacement (AVR) and PH to be a marker for poor prognosis. 6,7,[9][10][11]13,14 Therefore, assessment of PH is important for risk stratification, with PH being one of the components of the logistic EuroSCORE and the EuroSCORE II.…”
Section: Introductionmentioning
confidence: 99%
“…9 ) Thus, stroke remains the most devastating complication of TAVI. Since the prognosis of patients who benefit the most from TAVI is likely not only determined by AS severity, but also by multiple comorbidities, and possibly by the extent of extravalvular cardiac damage, 10 biomarkers that would implement clinical scores to identify patients at risk of major cardiovascular events, including stroke, or death could be very useful. Importantly, although valve replacement clearly improves patient outcome, 11,12 baseline comorbidities if left sub-optimally treated or myocardial damage might indeed, in specific cases, be the main cause of poor outcome.…”
mentioning
confidence: 99%